Ethnomedicinal plants used by Kanikkars of Agasthiarmalai Biosphere Reserve, Western Ghats - Tresina Soris2, A. Maruthupandian2 and V.R. Mohan2*, S. Lalitha Rani1, V. Kalpana Devi2, P. (Journal of Ecobiotechnology, 2011)
The study has been carried out in Agasthiarmalai Biosphere Reserve, Western Ghats, Tamil Nadu. Kanikkars, the predominant tribal community has their settlements in different areas in the Biosphere. A total of 174 medicinal plants belonging to 69 families are identified which have been employed by the tribal community for the treatment of various ailments.